Hyperuricemia and Gout: An Overview of Common Medical Condition - Alfazi, Raed Muawwadh Aifan; Almutairi, Talal Nasser; Al-Dosari, Ibrahim Saad Mohammed; Almutairi, Rasmi Obaid; Aleid , Afnan Mohammed; Ammash, Shatha Ali Ahmed; Almutari, Muhanna Safar Musleh; Madkhaly, Ghaniyah Mohammed Hussien (Journal of Ecohumanism, 2024)
Background: Hyperuricemia, defined as elevated serum uric acid levels (>6 mg/dL in women, >7 mg/dL in men), affects approximately 38 million Americans, with rising global prevalence due to Westernized diets and lifestyles. While often asymptomatic, hyperuricemia is associated with gout, nephrolithiasis, and systemic conditions like hypertension, metabolic syndrome, and cardiovascular disease. It results from increased uric acid production, decreased renal excretion, or a combination of both. Aim: This article provides a comprehensive overview of hyperuricemia, focusing on its etiology, pathophysiology, clinical manifestations, and management strategies, with an emphasis on gout and nephrolithiasis. Methods: The review synthesizes current literature on hyperuricemia, including its epidemiology, mechanisms, diagnostic evaluation, and treatment options. It also examines the role of dietary, genetic, and pharmacological factors in disease progression and management. Results: Hyperuricemia is primarily managed through lifestyle modifications and pharmacological interventions. First-line treatment includes xanthine oxidase inhibitors like allopurinol, while uricosuric agents and recombinant uricase drugs are reserved for refractory cases. Dietary education, particularly a low-purine, low-fructose diet, is crucial for prevention and management. Complications such as gout, nephrolithiasis, and chronic kidney disease require tailored interventions, including urate-lowering therapy and urinary alkalinization. Conclusion: Hyperuricemia is a multifactorial condition with significant implications for gout, nephrolithiasis, and systemic health. Effective management requires a combination of lifestyle changes, pharmacological therapy, and patient education. While asymptomatic hyperuricemia often does not require treatment, symptomatic cases necessitate individualized care to prevent complications and improve quality of life.